THE VALLEY OF ASHES IN THE GREAT GATSBY:A SYMBOLIC REPRESENTATION OF THE HIDDEN COSTS OF THE AMERICAN DREAM - Marupova Mavluda Umarjonovna (International Journal of Literature and Language Studies, 2026)
This article examines F. Scott Fitzgerald's use of the Valley of Ashes in The Great Gatsby (1925) as a sustained and multifaceted symbol of the concealed human and moral costs embedded within the ideology of the American Dream. Drawing upon close textual analysis alongside established critical frameworks in literary symbolism, social critique, and American Studies, this study argues that the Valley of Ashes functions not merely as a geographical backdrop but as an indispensable narrative and ideological counterweight to the opulence of East Egg and West Egg. The industrial wasteland, presided over by the faded eyes of Doctor T. J. Eckleburg on a decaying billboard, embodies the exploitation of the working class, the collapse of moral vision, and the corrosive spiritual bankruptcy that Fitzgerald identified as lying beneath the surface of 1920s prosperity. By situating this symbol within its broader socio-historical context — the rise of consumer capitalism, urbanization, and the myth of meritocratic upward mobility — this article demonstrates how Fitzgerald crafted a profoundly critical portrait of American modernity. The analysis reveals that the Valley of Ashes anticipates later theoretical frameworks concerning class, ideology, and the spectacle of wealth, and that its symbolic resonance remains urgently relevant to contemporary debates about inequality, environmental degradation, and the enduring mythology of limitless economic aspiration.